Persepsi Wajib Pajak Mengenai Korupsi, Penegakan Hukum dan Sikap Rasional Terhadap Tingkat Kepatuhan Wajib Pajak - Herlina, Saskia; Rodiah, Siti (Jurnal Akuntansi dan Keuangan, 2024)
The purpose of this study was to investigate how taxpayers' views on corruption, law enforcement, and reasonable attitudes affect their level of compliance with tax obligations. This study used a sample of 100 taxpayers registered at KPP Pratama Pekanbaru Tampan. This research uses the accidental sampling method, which involves selecting participants based on chance and not based on certain criteria. This means that anyone who is encountered during the research is considered a suitable data source. The sample size was determined using the Slovin formula. Data were collected through the use of questionnaire techniques and analyzed using SPSS statistical software, specifically version 25. The study employed various data analysis techniques, including validity test, reliability test, classical assumption test, multiple linear regression test, t-test, and coefficient of determination. The results show that the independent variables, namely perceptions of tax corruption, law enforcement, and rational attitudes, jointly affect the dependent variable, namely taxpayer compliance.